The Comparison of Peripheral Blood Morphology and Ferritin Level in Pregnancy Woman with Anemia Living in Lowland and Highland Areas - Yulfa Rizki Amita; Eddy Hartono; Syahruni Syahrir; Firdaus Hamid; Samrichard Rambulangi; Elizabet Catherine Jusuf (Indonesian Journal of Obstetrics & Gynecology Science, 2022)
Objective: Differences in the morphology features of red blood cells in population groups who live in the lowlands areas and the highlands areas will affect the diagnosis and appropriate therapies. Methods: The method used is a cross-sectional study of 75 pregnant women (6-38 weeks gestational age) with anemia living in highland and lowland areas found at Massenrempulu Hospital and Sitti Khadijah I Hospital. Anemia in pregnant women is diagnosed as a hemoglobin level less than 11gr/dl in the 1st and 3rd trimesters or less than 10.5 gr/dl in the 2nd trimester. The patient's blood sample was taken intravenously and performed serological and peripheral blood examination. Data were processed using the SPSS program, analyzed using univariate and multivariate tests.Results: In both results of the parametric and nonparametric test, ferritin levels showed a significant difference (p = 0.001), higher in the lowland areas group subjects (15.44 ± 36.92) compared to the highland areas group subjects (9.55 ± 30.16). There were no significant differences in morphology features (p> 0.05) between both groups.Conclusion: This study showed no significant differences in morphology features between the two groups. The lowland areas group subjects had a significantly higher ferritin level than that of the highland areas group subjects.Perbandingan Gambaran Morfologi Darah Tepi Pasien Gravid dengan Anemia Yang Tinggal di Pesisir Pantai dan Daerah PegununganAbstrakTujuan: Perbedaan ciri morfologi sel darah merah pada kelompok populasi yang tinggal di dataran rendah dan dataran tinggi akan mempengaruhi diagnosis dan terapi yang tepat.Metode: Metode yang digunakan adalah studi potong lintang pada 75 ibu hamil (usia kehamilan 6-38 minggu) dengan anemia yang tinggal di dataran tinggi dan dataran rendah yang ditemukan di RS Massenrempulu dan RS Sitti Khadijah I. Anemia pada ibu hamil didiagnosis berdasarkan kadar hemoglobin kurang dari 11gr/dl pada trimester I dan III atau kurang dari 10,5 gr/dl pada trimester II. Sampel darah pasien diambil secara intravena dan dilakukan pemeriksaan serologis dan darah tepi. Data diolah menggunakan program SPSS, dianalisis menggunakan uji univariat dan multivariat.Hasil: Pada hasil uji parametrik dan nonparametrik, kadar feritin menunjukkan perbedaan yang secara signifikan (p = 0,001), lebih tinggi pada subjek kelompok dataran rendah (15,44 ± 36,92) dibandingkan dengan subjek kelompok dataran tinggi (9,55 ± 30,16). Tidak ada perbedaan yang signifikan dalam morfologi darah tepi  (p> 0,05) antara kedua kelompok.Kesimpulan: Penelitian ini tidak menunjukkan perbedaan morfologi yang signifikan antara kedua kelompok. Subyek kelompok dataran rendah memiliki kadar feritin yang jauh lebih tinggi dibandingkan dengan subjek kelompok dataran tinggi.Kata kunci: Morfologi darah tepi, kehamilan, anemia, dataran rendah, dataran tinggi